Physical Therapy Interventions for Gait and Balance in Charcot-Marie-Tooth Disease: A Scoping Review - Roberto Tedeschi; Danilo Donati; Federica Giorgi (Life)
Background: This scoping review aims to map and summarise physical therapy interventions specifically targeting gait and balance in individuals with Charcot-Marie-Tooth disease (CMT), highlighting commonly applied strategies, methodological limitations, and clinical implications. Charcot-Marie-Tooth disease (CMT) is a hereditary neuropathy characterised by progressive motor and sensory impairment, often resulting in reduced mobility, muscle weakness, balance deficits, and fatigue. Although pharmacological options remain limited, rehabilitation is increasingly recognised as a key component of disease management. However, the scope, type, and effectiveness of rehabilitative interventions in CMT remain poorly mapped. Methods: This scoping review was conducted in accordance with the Joanna Briggs Institute (JBI) methodology and the PRISMA-ScR guidelines. Five databases (PubMed, Cochrane, PEDro, Scopus, and Web of Science) were systematically searched up to March 2024. Studies were eligible if they involved participants with CMT undergoing rehabilitation interventions aimed at improving functional outcomes. Data extraction focused on study characteristics, methods, outcome measures, and results. Results: Eleven studies met inclusion criteria, comprising case reports, cohort studies, and two randomised controlled trials. Interventions included aerobic training, strength and balance exercises, videogame-based home programmes, and multidisciplinary rehabilitation. Most studies reported improvements in walking capacity (e.g., 6MWT, 10MWT), postural balance (e.g., BBS), and lower limb strength (e.g., MRC, dynamometry). Some also showed positive changes in fatigue and quality of life, though data were limited. Methodological heterogeneity and small sample sizes limited comparability and generalisability. Conclusions: Rehabilitation appears to yield meaningful improvements in key functional domains in people with CMT. Tailored, multimodal interventions show promise, though long-term benefits remain underexplored. Future research should adopt standardised protocols and outcome measures to better define best practices and optimise patient care.